2017
DOI: 10.1007/978-981-10-4310-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Development of Therapeutic dsP21-322 for Cancer Treatment

Abstract: Small activating RNAs (saRNAs) are a class of artificially designed short duplex RNAs targeted at the promoter of a particular gene to upregulate its expression via a mechanism known as RNA activation (RNAa) and hold great promise for treating a wide variety of diseases including those undruggable by conventional therapies. The therapeutic benefits of saRNAs have been demonstrated in a number of preclinical studies carried out in different disease models including cancer. With many tumor suppressor genes (TSGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…RNAa is a recently discovered mechanism of gene regulation that provides a new therapeutic tool for the treatment of cancer ( 13 , 23 ). Our previous study demonstrated that endogenous miR-1236-3p and miR-370-5p induce p21 expression in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…RNAa is a recently discovered mechanism of gene regulation that provides a new therapeutic tool for the treatment of cancer ( 13 , 23 ). Our previous study demonstrated that endogenous miR-1236-3p and miR-370-5p induce p21 expression in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents the RB protein from becoming phosphorylated and, thus, prevents transcription factor E2F from being active and driving the transcription of genes involved in the S-phase of the cell cycle, such as DNA polymerase and cyclin A. 4 p21 can also induce apoptosis by suppressing the pro-apoptotic protein B-cell lymphoma-extra-large and activating caspase-3 and poly-ADP ribose polymerase. 4 Therefore, because of the anti-proliferative and pro-apoptotic roles of p21, there has been interest in targeting this protein in oncology.…”
Section: Different Approaches To Restoring Tumour Suppressor Functionmentioning
confidence: 99%
“…(Refs. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ) TP53 P53 Commonly referred to as the guardian of the genome, p53 is activated in response to cellular stress to induce cell-cycle arrest, apoptosis, DNA repair and cell senescence. Bladder cancer, Pheochromocytoma In vivo (Bladder) In vivo (Pheochromocytoma) Wang et al., Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…The argonaute protein Ago2 is recruited to the non-coding transcript that overlaps the promoter during both gene silencing and activation [18,19,20]. p21 was susceptible to RNA activation by dsP21-322 RNA in prostate adenocarcinoma cells (PC-3) [18,21,22].…”
Section: Experimental Design Of the Test Systemmentioning
confidence: 99%
“…[22] and the articles cited therein). Ago2 could be found in both nuclear and cytoplasmic compartments of the cells [22,21]. Molecular beacons that included energy transfer pairs of Alexa Fluor 633 and SQ as dark acceptor (that is the molecule named BHQ3) were used before for direct probing of unamplified genomic DNA by homogeneous hybridization using two-color fluorescence cross-correlation technique [24,25] and for detecting microRNA122 in live cells [23].…”
Section: Experimental Design Of the Test Systemmentioning
confidence: 99%